Assembly of substituted phenanthridines via a cascade palladium-catalyzed coupling reaction, deprotection and intramolecular cyclization. Issue 23 (17th February 2016) - Ge, Jun; Wang, Xiaojian; Liu, Tianqi; Shi, Zeyu; Xiao, Qiong; Yin, Dali
Abstract : A practical method for one-pot synthesis of substituted phenanthridines is described. Via this method, a series of substituted phenanthridines are obtained in good yields with remarkable functional groups compatibility. Abstract : The discovery and development of a general method for the one-pot synthesis of substituted phenanthridines is presented. In the presence of Pd(PPh3 )4, accessible precursors undergo a Suzuki cross-coupling reaction with 2-(Boc-amino)benzeneboronic acid pinacol ester and then spontaneously undergo deprotection and intramolecular condensation to form the corresponding phenanthridines in one step. This reaction has a wide range of substrates with various functional groups, and the corresponding products have been obtained in good yields.